High performance near ultraviolet emitter based on phenanthroimidazole via substitutions at C6- and C9-positions. (January 2017) - He, Dan; Yuan, Yi; Liu, Bin; Huang, De-Yue; Luo, Cheng-Yuan; Lu, Feng; Tong, Qing-Xiao; Lee, Chun-Sing
Abstract: A novel near ultraviolet (NUV) emitter, PIBCz, was designed and synthesized by attaching C3-position of the weak electron-donating N-phenylcarbazole group to C6- and C9-positions of phenanthroimidazole (PI) unit for limiting the molecular conjugation and intramolecular charge transfer (ICT) process. The new emitter exhibits strong NUV emission both in solution and thin film as well as good thermal and morphological stability. The PIBCz-based non-doped device shows a perfect color purity of CIE (0.15, 0.05), a very low turn-on voltage of 2.7 V and a maximum external quantum efficiency (EQE), current efficiency (CE) and power efficiency (PE) of 2.74%, 1.28 cd A −1 and 1.12 lm W −1, respectively, which is comparable to state-of-the-art non-doped OLEDs in similar color gamut. This work demonstrates that effective management of ICT process is a valuable strategy to develop high efficiency NUV emitters. Graphical abstract: Highlights: A NUV emitter with narrow FWHM, high quantum yields and good thermal properties is synthesized. The non-doped NUV OLED achieves a CEmax, PEmax and EQEmax of 1.28 cd A −1 1.12 lm W −1 and 2.74% respectively. It exhibits favorable color-purity with coordinates of (0.15, 0.05), low turn-on voltage and slight efficiency roll-off. The first time to exploit C6- or C9-substitutions of PI unit for constructing high performance NUV emitters.